THE PERSONALITY AND STATE GOVERNMENT OF AMIR TEMUR IN HISTORICAL SOURCES (Modern education and development, 2025)
This article analyzes historical sources on the personality and state administration of Amir Temur. Amir Temur appeared as a great commander, distinguished by his military-political activity, justice and a strong state administration system. The study reveals his personal qualities, including a style of governance based on justice, his role as a patron of science and art, and his contribution to the development of international trade and economy. It highlights how the centralized management system and military strategies created on the basis of the "Temur regulations" served to strengthen the state at that time and its global recognition. Also, information about Amir Temur in Eastern and Western sources is comparatively studied and his role as a statesman is assessed. This work aims to show that Amir Temur is not only a historical figure, but also an example for today's state administration and strategic planning.